Quercetin ameliorates chromium toxicity through improvement in photosynthetic activity, antioxidative defense system; and suppressed oxidative stress in Trigonella corniculata L. - Aslam, Muhammad Ashfaq; Ahmed, Shakil; Saleem, Muhammad; Shah, Anis Ali; Shah, Adnan Noor; Tanveer, Mohsin; Ali, Hayssam M.; Ghareeb, Rehab Y.; Hasan, Mohammad E.; Khan, Jallat (Frontiers in Plant Science, 2022)
Environmental stresses, including heavy metals accumulation, have posed an immense threat to the agricultural ecosystem, leading to a reduction in the yield of crucial crops. In this study, we evaluated the role of quercetin (Qu) in the alleviation of chromium (Cr) stress in Fenugreek (Trigonella corniculata L.). Different levels of Qu were prepared during the experiment, i.e., 15, 25, and 40 μM. For Cr toxification in potted soil, potassium chromate (K2Cr2O7) was used. Cr toxification reduced growth of T. corniculata seedlings. Cr stress also reduced fiber, ash, moisture, carbohydrate, protein, fats, and flavonoid contents. However, seed priming with Qu improved growth and physiochemical characteristics of T. corniculata seedlings grown in normal and Cr-contaminated soil. Seed priming with Qu escalated intercellular CO2 concentration, stomatal conductance, transpiration rate, and photosynthetic rate in T. corniculata seedlings. Application of Qu also increased the activity of antioxidative enzymes, i.e., superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and peroxidase (POD) in T. corniculata seedlings exposed to normal and Cr-contaminated soil. Application of Qu incremented the activity of SOD, POD, CAT, and APX, which were increased by 28, 22, 29, and 33%, respectively, in T. corniculata grown in Cr-toxic soil as compared to control treatment. Chromium stress alleviation was credited to the enhanced activity of the antioxidative defensive system in T. corniculata seedlings. It is proposed that Qu supplementation can be used to mitigate other abiotic stresses in plants.